Designing the competitive advantage model to Iranian football clubs based on teams’ reputation - Deheshti, M.; Morteza Azimzadeh, S.; Mirza Zadeh, Z. S.; Alimohammadi, H. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The objective of the present study was to design a competitive advantage model for Iranian football clubs based on teams’ reputation. In order to explore the components of the model, two rounds of Fuzzy Delphi staged by a half-open researcher-made questionnaire. The results of data analysis of two Fuzzy Delphi rounds indicated that, in the experts’ views, the most important components of club reputation were public relations (media and social relations), identity and brand image of the club, performance, tradition, social responsibility, fan orientation, quality of management and financial health of the team or football club. Furthermore, the most important competitive advantage based on team reputation in terms of experts includes the components of efficiency, responsiveness, innovation, quality and loyalty of fans. The model also demonstrated that the club reputation will lead to a competitive advantage through the fans’ satisfaction.